Islamic Financial Literacy Index of Students: Bridging SDGs of Islamic Finance - Arief Dwi Saputra; Alfina Rahmatia (Institute for Economic and Social Research, 2021)
This research aims to measure the level of Islamic financial literacy among students by reviewing 2 dimensions, 8 variables, and 33 indicators obtained from literature studies and experts. This study applied mix method to qualitative and quantitative data with a total sample of 273 respondents. The data were obtained from interview and online FGD and then processed by word similarity analysis as well as validity and reliability tests, the results of which are used as reference and conclusion. The analysis shows that the level of understanding of financial literacy among students remains significantly low, proven by the value of the interpretation of respondents reaching below 40% despite valid and reliable variables and indicators. Meanwhile, the analysis of the relationship between each variable that consists of supporting indicators shows that each variable affects one another. This study generates a financial literacy index serving as a measuring tool in bridging the SDGs of Islamic Finance. It implies the necessity of increasing the understanding of Islamic finance with the concept of literacy for students as an agenda to achieve a demographic bonus.